Biological Importance, Therapeutic Benefit, and Medicinal Importance of Flavonoid, Cirsiliol for the Development of Remedies against Human Disorders - Patel, Dinesh K. (Current Bioactive Compounds, 2022)
Background: Phytochemicals are pure chemical compounds found to be present in different plants part such as leaves, fruit, flower, seeds and the whole plant. These pure plant-based chemicals are having power to treat all disorders of the human beings and other higher animal species on earth. Flavonoidal compounds are responsible for the attractive color and important biological properties of plant material. Flavonoids are having a potential role in the treatment of numerous health complications of human beings. Antioxidant properties are one of the best pharmacological properties of all classes of flavonoidal compounds. A significant amount of these flavonoidal compounds are needed in our daily routine diet. Methods: Cirsiliol also called 5,3′,4′-trihydroxy-6,7-dimethoxyflavone is a flavonoidal class chemical found to be present in different plants including Salvia guaranitica. Various literature databases have been searched to know the biological potential of the cirsiliol in medicine. Different scientific research data of cirsiliol have been collected from various literature sources and analyzed in the present work. Detail pharmacological activities of cirsiliol in medicine have been evaluated in the present work through literature data analysis of various scientific research works. However analytical data has also been collected and analyzed in the present work through different literature sources. Results: From the collected data, it was found that cirsiliol is present in the plants such as Artemisia campestris, Artemisia scoparia, Centaurea jacea, Centaurea phyllocephala, Crossostephium chinense, Dracocephalum tanguticum, Eupatorium lindleyanum, Hyptis pectinata, and Iris germanica. Pharmacological data analysis revealed the biological importance of cirsiliol against cancer, inflammatory diseases, obesity-related insulin resistance, and respiratory disorders. However, the biological potential on ileum, benzodiazepine receptor, arachidonate 5-lipoxygenase, and xanthine oxidase has also been well summarized in the present investigation. High-performance liquid chromatography, bioactivity-guided isolation techniques, UPLC-ESI-MS/MS, LCMS and HPLC, and other forms of chromatographic techniques have been applicable for the analysis of cirsiliol in the various plants material. Conclusion: The present investigation revealed the biological importance and therapeutic benefit of cirsiliol in medicine for the development of better remedies against human disorders.
Keywords: human disorders